Specifics of Brand as Linguocultural Unit (Tula Text of Culture) - G. V. Tokarev (Научный диалог, 2023)
The semantic and pragmatic features of the brand as a linguocultural unit are described. The relevance of the study lies in the fact that considering the brand as a linguistic and cultural unit replenishes knowledge about the means that objectify the process of interaction between language and culture. It has been established that the assignment of this status to a language unit is possible when it is included in the system of everyday culture and has acquired one of its functions — self-presentation. The study of the properties of the brand was carried out on the material of the Tula subculture, in which about 20 such units were identified. In the course of the study, the brand is defined as a linguocultural sign that represents a subculture and participates in the process of its identification. Branding strategies for identifying the Tula culture are defined: appeal to specialties, samovar weapons, as well as precedent names. It has been established that the brand models culture, influences the peculiarities of its perception. It was revealed that the brand is characterized by such features as uniqueness, exclusivity, typicality, which distinguish it from a number of similar phenomena, ensure its expectation and understandability. It is proved that the semantics of the brand is characterized by concreteness, appraisal, emotiveness. It is concluded that brands represent the value dominants of culture: in Tula culture, they include craftsmanship, protection of the Fatherland, and the preservation of spiritual traditions.